Genetic characteristics of loggerhead turtles in the coastal corridor of the North West Pacific, around the Cape Muroto, Japan - Ishihara, Takashi; Kamezaki, Naoki; Hirai, Saya; Matsuzawa, Yoshimasa; Hamabata, Tomoko; Ishizaki, Asuka; Dutton, Peter H. (Frontiers in Marine Science, 2024)
Genetic characteristics of North Pacific loggerhead turtles captured as bycatch in pound nets operating in Muroto, Kochi, Japan were sampled to identify and estimate stock structure of coastal foraging aggregations. Tissue samples were obtained from juvenile, subadult and adult turtles from 2005–2006 and 2008–2010. For each of the years, 100 samples were processed and approximately 820 bp of mitochondrial DNA control region were sequenced. Straight carapace length of the turtles ranged from 56.3– 99.1 cm and their life stages were identified based on previous estimates of the size at puberty (66.0cm) and maturity (82.1cm). A total of 487 out of the 500 samples yielded sequences of sufficient quality to identify five different haplotypes. We conducted mixed stock analysis (MSA) using Bayesian approaches to estimate the contributions of three potential source nesting Management Units (MU) to the Muroto foraging aggregation. There were no significant differences between haplotype frequencies among the different size classes and life stages, nor among the different years, thus the haplotype frequencies were combined for the MSA. The MSA was run with and without consideration of MU size and distance, which resulted in similar MSA estimates. A >50% contribution was estimated from the Yakushima MU, and 40% from the Mainland MU, with only minor contribution from the Ryukyu MU. The estimated contribution from Mainland MU and Yakushima MU were disproportionately larger than the relative abundance of nesting at these MUs compared with Ryukyu MU, demonstrating that closer MUs had a greater contribution than those from further away. The lack of differences found in haplotype frequency among life stages, suggests that both juvenile and mature loggerhead turtles that remigrate to Japanese waters have the tendency to utilize foraging grounds and migration routes near their natal waters.